NEIGHBORS’ SOIL CONSERVATION AND CROP PRODUCTION IN KENYA - Gathiaka, Kamau (European Scientific Journal, ESJ, 2012)
This paper looks at the extent to which neighborhood soil conservation efforts affect crop output in smallholder farms in Kenya. Neighborhood soil conservation efforts are proxied by fertilizer application, grass stripping and soil ridging by neighboring farmers, all measured at the village level. Regression method was applied to primary data collected from Nyeri, a rural district in Kenya, to estimate crop production effects of neighbors‟ soil conservation efforts on individual plots. The results indicate that neighborhood fertilizer usage significantly increases crop production in smallholder agriculture.